Smoking attitudes and affecting factors of the nurses working in turgut ozal medical center - Aylaz, R.; Hacıevliyagil, S.; Durdu, A. (Journal of Dependence, 2008)
Objective: This study aimed to determine the smoking rate, cigarette addiction status of smokers, and risk factors related to smoking behavior among nurses working in a university hospital. Method: A survey was conducted under observation at Inonu University, Faculty of Medicine, Turgut Ozal Medical Center between June 2006 and August 2006. A questionnaire consisting of socio-demographic characteristics and the Fagerstrom nicotine addiction test was administered to the nurses. Findings: Smoking habit was found to be 54.4% among nurses (42.1% among females, 61.7% among males). Nurses were found to smoke more in hospital settings (59.4%). A significant difference was found between the smoking behavior of nurses according to their educational background (p
Keywords: cigarette; nurse; factor